1990
DOI: 10.1002/srin.199000353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxide scales on heat transfer in secondary cooling zones in the continuous casting process, part 2: determination of material properties of oxide scales on steel under spray‐water cooling conditions

Abstract: In order to model heat transfer from the slab to the cooling agent in the continuous casting process the thermophysical properties of the surface layer must be taken into account. For this purpose thermal conductivities and thermal diffusivities of wustite as well as of two carbon steels were measured. The oxide scale growth for six steels was measured as a function of time and at temperatures between 900 and 1200°C in air and in steam. Complex heterogeneous oxide scales were examined by optical and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
2
17
0
1
Order By: Relevance
“…For such mathematical simulations, the thermal conductivity and diffusivity of the iron oxide scale are the most important thermophysical properties. 4) To date, to the best of the authors' knowledge, there have been six reports on the thermal conductivity/diffusivity of iron oxide scales; [5][6][7][8][9][10] each has reported that the thermal conductivities/diffusivities of iron oxide scales are smaller than those of steel. Three of these studies have obtained the thermal diffusivities of single-phase samples of sintered iron oxides as functions of temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such mathematical simulations, the thermal conductivity and diffusivity of the iron oxide scale are the most important thermophysical properties. 4) To date, to the best of the authors' knowledge, there have been six reports on the thermal conductivity/diffusivity of iron oxide scales; [5][6][7][8][9][10] each has reported that the thermal conductivities/diffusivities of iron oxide scales are smaller than those of steel. Three of these studies have obtained the thermal diffusivities of single-phase samples of sintered iron oxides as functions of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these studies have obtained the thermal diffusivities of single-phase samples of sintered iron oxides as functions of temperature. [5][6][7] However, there are large discrepancies between the values and temperature dependencies. With respect to FeO, for example, Slowik et al 5) and Akiyama et al 6) have reported that the thermal diffusivity shows a positive temperature dependence, whereas Takeda et al 7) find a negative temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…13) Taylor et al measured on FeO film with the thickness of 0.35 mm grown on a 1 mm-thick iron plate. Several other reports are also available about sintered samples of FeO, Fe3O4 and Fe2O3; [14][15][16][17] however, there are large discrepancies between the reported values. For example, the thermal diffusivity of FeO ranges from 4 to 7 × 10 -7 m 2 s -1 at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the thermal diffusivity of FeO ranges from 4 to 7 × 10 -7 m 2 s -1 at room temperature. 14,15) The difference might come from the difference in the sample preparation processes. Slowik et al 14) measured on sintered FeO samples with 32% porosity and estimated thermal diffusivities of FeO with no porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Los mismos autores (25) encontraron además que, en el caso de mantenerse una película estable de vapor, la presencia de una capa de óxido modifica la transferencia de calor sólo cuando dicha capa se mantiene adherida a la superficie y cubriendo más de un 90 % de la misma. En tal circunstancia, se debe considerar la resistencia térmica aportada por el óxido (26).…”
Section: Enfriamiento Por La Acción Directa Del Aguaunclassified